Beyond criminal law: The multiple constitution of addiction in Australian legislation. (October 2014) - Seear, Kate; Fraser, Suzanne
<x xml:space="preserve">Abstract</x> The role of the criminal law in the regulation of drugs and addiction is both well known and the subject of considerable academic debate. Judges are frequently enjoined to make decisions about different kinds of addictions, and the relationships between substance use, addiction, agency, subjectivity, responsibility, treatment and punishment. The criminal law is not the only legal realm in which such questions are being explored, however. Addiction figures in non-criminal contexts in various ways, including via statute, regulations, common law and the law of equity. The significance of how addiction is understood and managed in these non-criminal contexts is sometimes overlooked in academic research. Drawing upon research being undertaken in Australia, this article seeks to highlight the wide range of non-criminal contexts within which questions about "addiction" are regularly being asked. Using examples from Australian legislation, we draw attention to several fundamental tensions and inconsistencies in legislative approaches regarding addiction and ask how tensions and inconsistencies between legal realms may impact on the health, wellbeing and opportunities of affected individuals. In so doing, we seek to make a case for the importance of academic research beyond the criminal law, including comparative work across different legal realms where laws, standards of proof and rules of evidence may differ. We consider the assumptions that underpin (and emerge from) this legislation, raising questions about the role of the law in the production and management of addiction as "multiple", and the possible "effects" of the constitution of addictions beyond the criminal law.